THE EFFECT OF VISIONARY LEADERSHIP PRINCIPALS AND TEACHER WORK DISCIPLINE ON THE MOTIVATION OF TEACHERS' ACHIEVEMENT IN TSANAWIYAH MADRASAH - Sugesti DINAWATI (Journal of Education and Leadership in Education, 2022)
This study aims to determine the effect of the exogenous variable, namely Principal Visionary Leadership and Teacher Work Discipline on the endogenous variable, namely Teacher Achievement Motivation at Madrasah Tsanawiyah in Central Jakarta. The research method used is a causal survey and uses path analysis techniques. The target population in this study was 182 teachers, while the affordable population was 170 teachers and the research sample was 125 teachers. The research sample was determined by random sampling. The results showed that there were (1) there was a direct positive positive effect of the principal's visionary leadership on the achievement motivation of teachers in Madrasah Tsanawiyah se - Jakarta (2) There was a direct positive influence of teacher work discipline on teacher achievement motivation in Madrasah Tsanawiyah se - Central Jakarta (3 ) There is a direct positive positive effect of the principal's visionary leadership on the work discipline of teachers in Madrasah Tsanawiyah throughout Central Jakarta with the coefficient of determination of structural equation 1 which is 0.968 and structure 2 is 0.959.